Assessment of knowledge and attitudes towards safety events reporting among residents in a community health system. Issue 5 (3rd September 2018) - Singal, M.; Zafar, A.; Tbakhi, B.; Jadhav, N.; Alweis, R.; Bhavsar, H.
ABSTRACT: Background : Resident physicians are known to be infrequent reporters of patient safety events (PSE). Previous studies assessing barriers to resident PSE reporting have not considered possible cultural barriers faced by international medical graduates (IMG). This study aimed to assess the knowledge and attitudes of residents regarding PSE and possible barriers contributing to poor resident reporting. Methods : A cross sectional survey of all house staff undergoing post-graduate residency training at two independent community hospital based academic medical centers was conducted through an online questionnaire. Sample case vignettes were created to assess the residents' ability to identify safety events and classify them as near miss, adverse events or sentinel events and decide whether they were reportable. Results : The Reporting of PSE increased significantly by year of residency training (p < 0.005), with time taken to file a PSE being the strongest perceived barrier. There was no difference in PSE reporting between IMG's and non- IMG's. We identified major knowledge gaps with only 73.9%, 79.6% and 94.3% of respondents correctly identifying sentinel events, adverse events, and near misses, respectively. 58.1% of respondents did not think near misses were reportable. Conclusions : A lack of knowledge is the most important barrier towards PSE reporting. A different cultural background and lack of previous exposure to patient safety report by IMGs is not a significant barrier towards safety event reporting. In the short-term, it appears that focusing limited institutional resources on education rather than acculturation issues would have the greatest benefit.